Dry Land Agriculture in Chotanagpur - Srivastava, V.P.; Pandey, S.N. (Journal of Soil and Water Conservation, 2022)
Dry land agriculture is an efficient system of soil and crop management in theregions having low and erratic distribution of rainfall. In Chotanagpur, though this region receives total average annual rain-fall over 40" (1000 m.m. ) but suffers from draught. The Chotasnagpur region comprises of the Districts of Hazaribagh, Ranchi, Singhbhum, Palamau and Dhanbad. This region has to depend on vagaries of monsoon for Agriculture.